The unsung heroes - Aaseng, Nathan (Minneapolis Lerner Pub. Co., 1989)
Introduces little-known individuals responsible for advancing well-known business products, including the originators of Coca-Cola, Hoover vacuum cleaners, and Bingo.
Keywords: Businessmen -- Biography -- Juvenile Literature